Women in Punjabi Proverbs: Cultural Models, Gender Ideologies and Stereotyping: Cultural Models, Gender Ideologies and Stereotyping (Journal of Gender and Social Issues, 2020)
A culture is well represented by its language, and within language, proverbs best summarize the cultural values and beliefs. This research is a study of Punjabi proverbs highlighting the embedded ideologies pertaining to male dominance in Punjabi culture. A collection of more than 500 gender-biased Punjabi proverbs are selected for the research from different archives. Out of 534 proverbs, sixty (60) are selected on the basis of stereotypical representation of women. The data is further divided into sub-categories: stereotype, gender bias, insult, objectification and violence. These sub-categories are analyzed in accordance with the cultural models to scrutinise the stereotypical attitude, predominantly with regards to women in Punjabi proverbs.
Keywords: Punjabi proverbs, gender ideologies, cultural models, sexism, stereotypes, violence